The effect of fluctuating maskers on speech understanding of high-performing cochlear implant users. (3rd May 2016) - Zirn, Stefan; Polterauer, Daniel; Keller, Stefanie; Hemmert, Werner
Abstract: Objective : The present study evaluated whether the poorer baseline performance of cochlear implant (CI) users or the technical and/or physiological properties of CI stimulation are responsible for the absence of masking release. Design : This study measured speech reception thresholds (SRTs) in continuous and modulated noise as a function of signal to noise ratio (SNR). Study sample : A total of 24 subjects participated: 12 normal-hearing (NH) listeners and 12 subjects provided with recent MED-EL CI systems. Results : The mean SRT of CI users in continuous noise was −3.0 ± 1.5 dB SNR (mean ± SEM), while the normal-hearing group reached −5.9 ± 0.8 dB SNR. In modulated noise, the difference across groups increased considerably. For CI users, the mean SRT worsened to −1.4 ± 2.3 dB SNR, while it improved for normal-hearing listeners to −18.9 ± 3.8 dB SNR. Conclusions : The detrimental effect of fluctuating maskers on SRTs in CI users shown by prior studies was confirmed by the current study. Concluding, the absence of masking release is mainly caused by the technical and/or physiological properties of CI stimulation, not just the poorer baseline performance of many CI users compared to normal-hearing subjects. Speech understanding in modulated noise was more robust in CI users who had a relatively large electrical dynamic range.